علامہ نیاز فتح پوری اور ان کا سفر کیمبل پور - Rubani Aziz, Ghulam (Tabeer e Nau, 2025)
Allama Niaz Fatehpuri is known as an important figure in the history of Urdu literature. Allama Niaz Fatehpuri, with his critical, creative and scholarly abilities, created a movement in the world of Urdu poetry and literature in the first half of the twentieth century. His critical insight and extraordinary creative abilities increased the value of many genres of poetry and prose and in the fields of translation also his impact is valuable. His literary magazine "Nigar" undoubtedly nurtured many generations. He undertook a long journey from Bhopal to Campbellpur in 1929 at the behest of Professor Ghulam Rabbani Aziz and Dr. Ghulam Jilani Barq. In the present article, the details of his literary journey have been presented in detail by the renowned writer Professor Ghulam Rabbani Aziz. The details reveal many new things about Allama Niaz Fatehpuri, which are of importance to researchers and literary historians. In view of this importance, this unpublished article is being preserved in “Tabeer-e-Nau”.